Frequency of perforated appendix in patients presenting with acute appendicitis in Surgical C Ward, Ayub Teaching Hospital - Khalid, Bilal; Malik, Irfan; Khan, Zakir; Farooq, Umar; Shehzad, Munhill; Misbah Ullah (Indus Journal of Bioscience Research, 2025)
Background: Acute appendicitis is a common surgical emergency, with perforation being a serious complication that increases morbidity and mortality. Identifying risk factors for perforation and allocation of adequate healthcare resources is crucial for timely intervention, particularly in diverse socioeconomic settings. While clinical diagnosis remains challenging, understanding demographic and comorbidity-related associations can improve patient outcomes. Objective: To determine the frequency of perforated appendix in patients presenting with acute appendicitis in Surgical C Ward at Ayub Teaching Hospital. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from June 2024 to December 2024 at the Department of Surgery, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 127 patients aged 12–50 years with acute appendicitis were enrolled. Diagnosis was based on clinical criteria (fever >100°F, right lower quadrant pain >5 on scale, WBC count ≥10,000/mm³) and confirmed intra-operatively. Perforation was identified by purulent/feculent spillage, visible perforation, or abscess. Data on age, BMI, gender, residence, socioeconomic status, family history, diabetes, and hypertension were collected. Results: The mean age of patients was 30.70 ± 10.70 years, with 51.2% male representation. Perforated appendix was found in 19.7% of cases. Age >30 years (35.1% vs. 7.1%, p<0.001), BMI >25 kg/m² (36.4% vs. 6.9%, p<0.001), urban residence (30.0% vs. 7.0%, p=0.001), and comorbidities like diabetes (62.5% vs. 16.8%, p=0.008) and hypertension (54.5% vs. 7.4%, p<0.001) were significantly associated with perforation. Conclusion: Perforated appendicitis is significantly associated with older age, obesity, urban residency, higher socioeconomic status, and metabolic comorbidities.